A Fully Computerized Method to Backup the Router Configuration File - Younis, Mohammed I.; Majeed, Ghassan H. (Al-Khwarizmi Engineering Journal, 2007)
This paper presents a fully computerized method to backup the router configuration file. The method consists of a friendly graphical interface programmed by Java programming language.    The proposed method is compared with the two existing methods, namely: TFTP server method and Copy/Paste method. The comparison reveals that the proposed method has many advantages over the existing ones. The proposed method has been implemented on Cisco routers (series 2500, 2600 and 2800).